Hip-hop is history - Questlove; Greenman, Ben (AUWA Books / MCD / Farrar, Straus and Giroux, 2024)
"A comprehensive fifty-year history of the hip-hop genre, from renowned artist and author of MUSIC IS HISTORY, Questlove"--